2020
DOI: 10.1016/j.biomaterials.2020.119833
|View full text |Cite
|
Sign up to set email alerts
|

Nano-particle mediated M2 macrophage polarization enhances bone formation and MSC osteogenesis in an IL-10 dependent manner

Abstract: Engineering a pro-regenerative immune response following scaffold implantation is integral to functional tissue regeneration. The immune response to implanted biomaterials is determined by multiple factors, including biophysical cues such as material stiffness, topography and particle size. In this study we developed an immune modulating scaffold for bone defect healing containing bone mimetic nano hydroxyapatite particles (BMnP). We first demonstrate that, in contrast to commercially available micron-sized hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
186
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(191 citation statements)
references
References 55 publications
4
186
1
Order By: Relevance
“…Similarly, it is likely that different non-viral gene delivery vectors have different propensities for stimulating a pro- or anti-inflammatory response, which might enhance or suppress the effect of their therapeutic cargo. This is supported by a recent study reporting that the size and shape of hydroxyapatite particles can be tuned to stimulate M2 macrophage polarization ( Mahon et al, 2020 ). A limited assessment might be possible to determine the effect of different non-viral gene delivery vectors on M1/M2 macrophage polarization; however, in vivo assessment would ultimately be required to better understand the relationship between non-viral gene delivery vectors and the immune response that they trigger.…”
Section: Discussionsupporting
confidence: 56%
“…Similarly, it is likely that different non-viral gene delivery vectors have different propensities for stimulating a pro- or anti-inflammatory response, which might enhance or suppress the effect of their therapeutic cargo. This is supported by a recent study reporting that the size and shape of hydroxyapatite particles can be tuned to stimulate M2 macrophage polarization ( Mahon et al, 2020 ). A limited assessment might be possible to determine the effect of different non-viral gene delivery vectors on M1/M2 macrophage polarization; however, in vivo assessment would ultimately be required to better understand the relationship between non-viral gene delivery vectors and the immune response that they trigger.…”
Section: Discussionsupporting
confidence: 56%
“…This is based on the fact that such amorphous surface layer generally forms for nanocrystalline HA samples synthesized by direct precipitation methods at ambient temperature. [48,72,73] It can also be seen that the resonance of the 31 P SP MAS ssNMR spectrum of the nnHA scaffold (FWHM = 2.0 ± 0.2 ppm) is largely wider than that of a stoichiometric hydroxyapatite sample such as iHA powder (FWHM = 0.8 ± 0.1 ppm) ( Figure 3A). Based on the above, the hydroxyapatite nanoparticles of the nnHA MEW scaffold, Figure 3.…”
Section: Coated Scaffold Groups Contain a Crystalline Ha Core And Bonmentioning
confidence: 92%
“…[45][46][47] Appropriately sized nHA particles can also preferentially polarize human macrophages toward an M2 phenotype and enhance production of the anti-inflammatory cytokines such as IL-10. [48] The role of HA particle size has also been investigated in the 3D printing of composite polycaprolactone-HA (PCL-HA) blends, with enhanced proliferation and alkaline phosphatase (ALP) activity of MSCs seen with nanoparticles compared to microparticles. [49] Remarkably, particle size has not only been shown to be an important cue for MSC osteogenesis but also plays a role in suppressing undesired cellular outcomes in bone.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that biomaterials with special components and surface topographies can also induce macrophage polarization, switching from pro-inflammatory M1 to anti-inflammatory M2 types [ 29 ]. In addition, the polarization induced by the materials may be closely related to their osteogenic activity.…”
Section: Introductionmentioning
confidence: 99%